Substitution of peat with municipal solid waste compost in watermelon seedling production combined with fertigation - Papamichalaki, Maria; Papadaki, Anastasia; Tzortzakis, Nikos G. (My University, 2014)
Interest in reusing organic residues as substrate medium in nurseries has increased worldwide as peat availability has been reduced over time. In this study, the effect of fertigation and/or a partial substitution of peat with municipal solid waste compost (MSWC) on the emergence, growth, and nutrition of watermelon (Citrullus lanatus L.) seedlings were tested. The MSWC extracts (MSWC:water at 10-1 and 10-2 dilutions) maintained seedling germination. Under nursery conditions, six media prepared from commercial peat and MSWC were further assessed in conjunction with nutrient application as basic fertilizer (BF) or hydro fertilizer (HF). Adding MSWC to the substrate inhibited seed emergence and mean germination time, whereas fertigation maintained seed emergence in 15% MSWC but decreased in 45% MSWC. Adding 45% MSWC reduced seedling height, leaf number, and fresh weight. The HF increased fresh weight (up to 44%) and growth in seedlings cultivated in 15% MSWC. Leaf photosynthetic rate and stomatal conductance increased (up to 2.6-fold) in MSWC-based (< 45% MSWC) substrates, but no differences were observed in chlorophyll a, chlorophyll b, total carotenoid content, and leaf fluorescence. The HF reduced chlorophyll a and total carotenoids, but increased chlorophyll b content. The K, N, and Na content increased (ranging from 2-to 5-fold) when adding MSWC, whereas P content did not differ. Fertigation benefits seedling nutritive status. Low content (15% to 30%) of MSWC may act as an alternative substitute for peat with more positive effects if minerals are provided through HF.
Keywords: Citrullus lanatus; Compost; Growth; Municipal solid waste; Peat; Seed emergence; Watermelon